2017
DOI: 10.1186/s12902-017-0177-3
|View full text |Cite
|
Sign up to set email alerts
|

Androsterone glucuronide to dehydroepiandrosterone sulphate ratio is discriminatory for obese Caucasian women with polycystic ovary syndrome

Abstract: BackgroundAndrosterone glucuronide (ADTG) concentrations have been suggested as a marker of the effects of androgens at the target tissue level. As the mechanism for hyperandrogenemia in obese and nonobese polycystic ovary syndrome (PCOS) may differ, this study compared the different androgen parameters in non-obese compared to obese women with PCOS, and in normal subjects.MethodsEleven non-obese and 14 obese women with PCOS were recruited and compared to 11 control women without PCOS. Total testosterone, dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We found that reduced androsterone-glucuronide, a major metabolite of active androgens, 50 , 51 , 52 is associated with decreased TBS even after adjusting for DST-cortisol among premenopausal women with ACS. As a major adrenal androgen, DHEA-S is locally converted to the active androgens (testosterone and 5α-dihydrotestosterone) in bone tissues, where it is thought to exert biological effects via androgen receptors.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We found that reduced androsterone-glucuronide, a major metabolite of active androgens, 50 , 51 , 52 is associated with decreased TBS even after adjusting for DST-cortisol among premenopausal women with ACS. As a major adrenal androgen, DHEA-S is locally converted to the active androgens (testosterone and 5α-dihydrotestosterone) in bone tissues, where it is thought to exert biological effects via androgen receptors.…”
Section: Discussionmentioning
confidence: 78%
“… 56 Since most androgens are derived from the adrenal cortex, especially in women, 41 , 53 androsterone-glucuronide may reflect the entire action of adrenal androgens on target tissues. 50 , 51 , 52 It is, therefore, likely that reduced adrenal androgens contribute to deteriorated bone quality, independently of autonomous cortisol secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Medical diagnoses, age, gender, country, history of genital surgery, and contact with support groups are shown in Table 1 . Response rate in the dsd-LIFE study was 36.1% (Rohle et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dsd-LIFE is a multicentre cross-sectional clinical evaluation study mobilizing 16 partners in Germany, France, the Netherlands, Poland, Sweden, and the United Kingdom, of whom 14 were active recruiting sites. The methodological approach, including the process to ensure valid translation, is described in Rohle et al ( 2017 ). Adolescents (≥ 16 years) and adults with DSD were recruited from February 2014 to September 2015 via medical centers, the project website, and support group contact.…”
Section: Methodsmentioning
confidence: 99%
“… 81 ADT‐G, a metabolite formed during the metabolism of testosterone or dihydrotestosterone (DHT), is a major contributor to total androgen glucuronides in women, accounting for approximately 93%. 90 Elevated levels of ADT‐G in relation to dehydroepiandrosterone sulphate (DHEAS) have been identified as a potential marker of insulin resistance in obese women with polycystic ovary syndrome (PCOS), 91 and ADT‐G has also been suggested as a potential biomarker for peripheral hyperandrogenism, or excess of androgens, in adult women with acne. 92 A recent study has found that certain metabolites, including androgenic steroids, long‐chain fatty acids and microbiota‐produced compounds, are associated with insulin resistance in young, non‐obese females in Qatar, when compared to those without insulin resistance.…”
Section: Physical Activity Can Induce Long‐term Adaptations In Cellul...mentioning
confidence: 99%